2009
DOI: 10.1364/oe.17.019006
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz time-domain spectroscopy as a tool to monitor the glass transition in polymers

Abstract: We demonstrate the suitability of terahertz time-domain spectroscopy as a non-destructive, contact-free tool to monitor the glass transition in polymers--a core feature of the amorphous phase. Below the glass transition temperature T(g), segmental motions along the polymer chain are frozen due to the lack of free volume between neighboring macromolecules. We show that this transition also reflects in the temperature dependence of the refractive index at terahertz frequencies. Two domains can be identified, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…Both the amplitude and phase information of a sample can be obtained simultaneously through THz-TDS, without resorting to a complex analysis [2]. Previous studies demonstrated the powerful spectroscopic capability of THz-TDS in characterizing many materials, including polymers [3], explosive materials [4], solidstate materials [5,6], chemical compounds in liquids [7], ions [8], biomaterials [9], and even the material phase transitions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both the amplitude and phase information of a sample can be obtained simultaneously through THz-TDS, without resorting to a complex analysis [2]. Previous studies demonstrated the powerful spectroscopic capability of THz-TDS in characterizing many materials, including polymers [3], explosive materials [4], solidstate materials [5,6], chemical compounds in liquids [7], ions [8], biomaterials [9], and even the material phase transitions [10].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of THz-TDS for NDT studies are the high penetration of THz electromagnetic waves into polymers [13][14][15][16][17][18], high sensitivity to the inter/intra molecular vibrations (especially for water) [18][19][20][21][22][23][24][25][26], and ability to estimate the materials dielectric properties without direct contact [27][28][29]. The THz spectra of various thermoplastics [13][14][15] and thermosets [16,17] measured by THz-TDS were reported.…”
mentioning
confidence: 99%
“…The THz spectra of various thermoplastics [13][14][15] and thermosets [16,17] measured by THz-TDS were reported. In contrast with FT-IR spectra, the THz spectra shows a few clear features to distinguish polymer molecular structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations